Penampilan Pertumbuhan dan Hasil Beberapa Genotipe Jagung Calon Hibrida Umur Genjah di Lahan Kering - ,, St. Subaedah; Numba, Sudirman; Saida, dan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2018)
Maize is commonly developed in dry land areas with limited irrigation water in Indonesia, thereby posing a threat to its poductivity. Thus, availability of early harvest varieties able to adapt to limited water is important. The aim of this study was to analyze the performance of maize hybrid genotypes candidates in dry land. The research was conducted from April to July 2016 at Gowa, South Sulawesi. The experiment was designed with a randomized complete block design consisting of 8 genotypes, namely GJ1, GJ2, GJ3, GJ4, GJ5, GJ6, GJ7, GJ8, and two control varieties, i.e., Bima 7 and Lamuru. The results showed genotypes GJ1, GJ6, GJ7 and GJ8 had higher plant growth as compared to Bima 7 and Lamuru. All genotypes were harvested less than 90 days. Genotypes GJ6, GJ7, and GJ8 yielded 6.85 tons ha-1, 6.51 tons ha-1 and 8.31 tons ha-1, respectively, which were higher 13-45% than the Lamuru control variety. Because this experiment was carried out in an optimun condition, it would be necessary to further study the three genotypes in drought stress conditions before being developed for early harvest and high yielding hybrid varieties.